(untitled) (Research, Society and Development, 2020)
This work aimed to carry out a theoretical reflection on the constitution of science, common sense and the relationships surrounding these two forms of thought. The thinker Boaventura de Souza Santos and his works were chosen due to the level of dedication on studies related to the theme. Therefore, the analysis involved a bibliographic survey of three works by the sociologist: (i) The critics to indolent reason: against the waste of experience; (ii) Renew the critical theory and reinvent social emancipation and (iii) A speech on the sciences. In his writings, Boaventura reveals a new social order which has begun from the epistemological crisis of the dominant paradigm, emerging a new paradigm that reveals the importance of common sense and other forms of knowledge. This is the result of little or no correspondence concerning parts of society, which has experienced a social transformation based on science, but which no longer accepts it as being objective, global, rational, deterministic, totalitarian and hegemonic. Science only is not enough for satisfying citizens’ desires. Therefore, the sociologist defends the renunciation of dissociating common sense and science, recognizing them as just two different types of knowledge, which play important roles and are structured within human knowledge as a whole, and not as an isolated manner such it had been thought for a long time.